SATUAN EKSPRESI PENAMAAN DAN PERSAMAAN WARNA DALAM PRODUK LIPSTIK - Elen Inderasari, Wahyu Oktavia (Kantor Bahasa Kalimantan Timur, 2019)
Lipstick is one of makeup elements used to give color to the lips to beautify women’s appearance. The purpose of this study is to describe expression units for the naming and similarity of colors in lipstick products. It focuses on semantic aspects. The method used in this study is a qualitative descriptive. Data collection techniques used is observation and notes taking. It applies the data analysis techniques in three stages, namely the process of finding, managing, and presenting the data. The results of the study show that there are (a) expression units of color in the lipstick products, (b) expression units of labeling the lipstick colors, and (c) expression units of the lipstick color likeness.